Ethnobotanical Study of Ethno-veterinary Medicinal Plants in YilmanaDensa and Quarit Districts, West Gojjam Zone, Amhara Region, Ethiopia - Alemneh, Derebe (Ethnobotany Research and Applications, 2021)
Background: In Ethiopia, about 90% of the animal population has been treated by traditional medicine derived from medicinal plants. Thus, for the sustainable use of the species there should be an exploration of unexplored areas of the country to present an output data for conservation planners and policy makers. The current study districts were one of the unexplored areas of the country. Methods: Reconnaissance survey was conducted from September 2015 to June 2016. General informants were selected systematically. Data were collected with semi-structured interviews, and observation. Consensus factor, fidelity level and ranking exercises were calculated to analyze the data. Results: Thirteen medicinal plants were recorded in the districts. Most of the species were herbs, non-cultivated, and used to treat cattle diseases. Leaves were the primary source of remedy. Most remedy was prepared by crushing from non-dried parts. Most of the remedy was administered through oral routes and used to treat gastrointestinal diseases. Stephania abyssinica showed the highest fidelity level for the gastrointestinal disorders whereas Phytolacca dodecandra was the most preferred. Overharvesting and agricultural land expansions were the major identified threats. Conclusion: Medicinal plants of the districts are under serious threats, and thus the species should be conserved by taking an immediate conservation action. Keywords: Healing potential, informant agreement, marketability, respondents